The effect of special exercises in the circular and iterative methods in developing the distinctive strength with speed for the lower limbs and the accuracy of scoring football in the halls - Ibrahim , Layth Ismael; Abdulrazak, Zahid Sbhee; Mohammed, Saher; Ahmed, Omar Saad (International Journal of Psychosocial Rehabilitation, 2020)
Football for the halls is one of the exciting and popular team games for young and old due to the effects, speed and suspense it has as a result of developing the level of players physically, skillfully and plans, which made those concerned call it the game of multiple talents, as it requires high mastery of the individual basic skills on the one hand and coordinating work with members of one team on the one hand Others. Since the progress has included most sporting events and games, football halls that possess an asset of interest and popularity have evolved in their planning aspects, where sound early skill building based on modern scientific principles is the most important factors and requirements of modern futsal.Physical fitness and its physical characteristics included an important role in the game and most scientists see that everything that happens in the game depends on the physical elements on which special fitness is built and it is not possible to play at a high level without this fitness.The element of strength is one of its important elements that have an effective impact for the player, which coaches need to focus on and develop as modern football players must possess it in a manner that serves the implementation of skills as quickly as possible, which has become a feature of modern play for most of the teams presented in the worldThe training unit that contains a number of exercises must set a scientific program for its application and practice in terms of the sequence of exercises, methods of implementation and repetition and times of work and rest in them, in order for the players to exercise them with more motivation and activity than it is, and that they are not used in a monotonous manner so as to send boredom in the hearts of the players. As the modern practical method advocated by sports training experts is to call for diversification in educational and training methods and methodsIn light of the foregoing, the importance of the research comes by using the exercises prepared by the researcher in the circular and iterative methods in developing the force marked by speed for the lower limbs and the accuracy of scoring football in the halls of the Diyala education team